Rate–Pressure Product and Cardiac Cachexia in End-Stage Heart Failure - Makoto Suzuki; Manami Kishimoto; Tomomi Horita; Akira Fujii; Satoru Hamada (Annals of Internal Medicine: Clinical Cases)
To address the effect of cardiac cachexia on the failing heart, we analyzed serial home-care monitoring of the rate–pressure product, as substitution of myocardial oxygen consumption, over 218 days in a 79-year-old man with a catecholamine-dependent end-stage dilated cardiomyopathy. At the end of his home-care visits, his body weight decreased to 37 kg from 55.2 kg (baseline). We found a linear reduction of the rate–pressure product accompanied by weight loss (r2 = 0.186; P = 0.0001), implying the progression of cardiac cachexia as a possible role in reducing myocardial oxygen consumption, which would mitigate energy deprivation of the failing heart.